1998
DOI: 10.1016/s0893-133x(97)00097-3
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter and Seasonal Variation in Blood Serotonin in Families with Obsessive-Compulsive Disorder

Abstract: The serotonin transporter (HTT) is a candidate gene for obsessive-compulsive disorder (OCD) that has been associated with anxiety-related traits. The long (1) and short (s) variants of theThe serotonin transporter (HTT = SLC6A4) is a plausible candidate gene for obsessive-compulsive disorder (OCD) and several other psychiatric disorders (Altemus et al. 1996;Lesch et al. 1995;Ogilvie et al. 1996). It has been associated with anxiety-related traits in two predominantly male samples (Gelernter et al. 1995;Ramam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(86 citation statements)
references
References 65 publications
5
79
2
Order By: Relevance
“…21 These results, along with some of the findings from previous human studies, [22][23][24] demonstrate a relationship between the 5-HTTLPR and 5-HT functioning in both human and nonhuman primates (but also see Naylor et al 25 and Jonsson et al 26 ). Although the 5-HTTLPR alleles are differentially active in vitro, relatively few studies have examined direct measures of CNS serotonin function in either humans or other animals.…”
Section: Molecular Psychiatrysupporting
confidence: 55%
“…21 These results, along with some of the findings from previous human studies, [22][23][24] demonstrate a relationship between the 5-HTTLPR and 5-HT functioning in both human and nonhuman primates (but also see Naylor et al 25 and Jonsson et al 26 ). Although the 5-HTTLPR alleles are differentially active in vitro, relatively few studies have examined direct measures of CNS serotonin function in either humans or other animals.…”
Section: Molecular Psychiatrysupporting
confidence: 55%
“…Therefore, we also characterized hormonal responses in subjects expressing either the long or short form of a functional polymorphism within the serotonin transporter gene. In vitro and in vivo studies have shown that tissue expressing the long form of the polymorphism expresses more transporter mRNA and exhibits 2-fold greater serotonin uptake compared to cells expressing the short form of the allele (Hanna et al 1998;Lesch et al 1997;Little et al 1998). Because the short allele is associated with reduced transporter activity (greater synaptic serotonin concentration), it is possible that persons expressing the shorter allele would have greater serotonergic activity and thereby greater HPA axis activation compared to persons expressing only the long form of the allele.…”
Section: Discussionmentioning
confidence: 99%
“…The serotonin transporter regulates the concentration of serotonin within the synaptic cleft and thereby modulates magnitude and duration of serotonin-induced postsynaptic mediated signals (Lesch and Mossner 1998). Recently a functional polymorphism has been described in the promoter region of the transporter, which modulates transcriptional activity of this gene as well as tissue expression of transporter activity (Hanna et al 1998;Heils et al 1997;Little et al 1998). Like the A118G polymorphism in the mu-opioid receptor, it is plausible that this functional polymorphism within the serotonin transporter is associated with altered HPA axis dynamics.…”
mentioning
confidence: 99%
“…Additionally, the uptake of 5-HT is approximately two-fold higher in cells containing the homozygous ll form of the 5-HTTLPR than either the ls or ss forms (Lesch and Mossner, 1998). Other factors, such as seasonal variation, also interact with the 5-HTTLPR genotype to influence both the uptake potential and expression of the SERT (Hanna et al, 1998). Despite the influence of genotype on SERT expression and uptake, genotype has not been demonstrated to have any effect on 5-HT binding affinity (Greenberg, 1999).…”
Section: Genetics Of Sertmentioning
confidence: 99%